Two full capacity generators—Why is the calculated emergency power system probability of failure on demand so high?. Issue 3 (13th November 2020) - Dowell, Arthur M. (Art)
Abstract: The probability of failure on demand (PFD) for an emergency generator system is important when electrical power is needed to protect humans from harm or to prevent equipment damage. To evaluate the PFD for an emergency power system (EPS), we must consider: All the components for the fuel, the controls, the transfer switches, and the circuit breakers in the emergency load feeders. The capability of the weekly, monthly, semiannual, annual, and four‐year inspections and proof tests to detect all the failure modes that can prevent correct operation of the generator system. Many common cause events may prevent both generators from starting or running: The fuel storage system. The generator control system including over‐voltage and overload protection. The downstream electrical system including the transfer switches and circuit breakers. Human action during maintenance and testing, such as leaving the transfer switches in test mode instead of automatic. While the EPS may be designed and operated according to NFPA 110, it is critical to evaluate and eliminate single points of failure. The paper will suggest opportunities to provide redundancy, to manage human error, and to improve inspections and proof testing to detect more failure modes.